2022
DOI: 10.1177/00846724221102198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of listening to Quran recitation on anxiety reduction in elective surgeries: A systematic review and meta-analysis

Abstract: Anxiety is a common unpleasant reaction among patients undergoing surgery. Many non-pharmacological methods such as spiritual strength are effective in preoperative anxiety management. This study aimed to assess the effects of listening to Quran recitation on reducing preoperative anxiety. A systematic review was performed in Medline, EMBASE, Cochrane Library, PsycINFO, Arab World Research Source, and other relevant databases to collect the data. Randomized controlled trials about the effects of listening to Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, the investigations conducted by Alorani and Alradaydeh (2017) and Che Wan Mohd Rozali et al (2022) underscore the positive influence of Quranic engagement on spiritual well-being and various mental health parameters, including depression, anxiety, and overall quality of life ( Alorani & Alradaydeh, 2017 ; Che Wan Mohd Rozali et al, 2022 ). The profound relaxation induced by Quranic recitation further aligns with the prospect of stress reduction and emotional well-being ( Gavgani et al, 2022 ; Nayef & Wahab, 2018 ). Additionally, the study conducted by Tobing et al (2022) highlights a positive relationship between the intensity of Quran reading and cognitive function in older individuals ( Tobing et al, 2022 ).…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, the investigations conducted by Alorani and Alradaydeh (2017) and Che Wan Mohd Rozali et al (2022) underscore the positive influence of Quranic engagement on spiritual well-being and various mental health parameters, including depression, anxiety, and overall quality of life ( Alorani & Alradaydeh, 2017 ; Che Wan Mohd Rozali et al, 2022 ). The profound relaxation induced by Quranic recitation further aligns with the prospect of stress reduction and emotional well-being ( Gavgani et al, 2022 ; Nayef & Wahab, 2018 ). Additionally, the study conducted by Tobing et al (2022) highlights a positive relationship between the intensity of Quran reading and cognitive function in older individuals ( Tobing et al, 2022 ).…”
Section: Discussionmentioning
confidence: 72%
“…Validity and reliability: In Iran, the Cronbach's alpha coefficient for the subscales of this test is in the range of 0.62 to 0.91, as well as the reliability coefficient of these factors in a retest method with a time interval of one week between 0.75 and 0.88. have obtained the results of factor analysis using principal components have shown that the selfregulation questionnaire has a seven-factor structure that includes positive refocusing of planning, positive evaluation of a broad perspective, acceptance, blaming others, blaming oneself, rumination, and catastrophizing. The content validity of the emotional regulation questionnaire was evaluated based on the evaluation of eight psychological experts, and Kendall's agreement coefficients for the subscales were calculated from 0.81 to 0.92 [28]. In Khodapanah et al's research (2016), Cronbach's alpha of negative (ineffective) strategies was 0.89.…”
Section: E Emotional Regulation Questionnairementioning
confidence: 99%
“…The review reveals that Awaad et al (2021) and Zin (2022) conducted studies which showed that Muslim lecturers and students who engaged in reciting the Quran had a strong and positive relationship with their well-being. Reciting the Quran can allow one to have a positive relationship with their well-being due to its potential psychological benefits, such as providing a sense of calm, reducing anxiety and stress (Zarea Gavgani et al, 2022), promoting positive thinking and spiritual connection, and offering a source of guidance and comfort in difficult times (Setiadi, 2023). A study by Kannan et al (2022) also indicates that the impact of listening to rhythmic verses of the Quran on the brain is similar with that of music and rhythmic therapy which can have healing properties and provide a sense of purpose and meaning to one's life.…”
Section: Reciting the Quranmentioning
confidence: 99%